ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA PADA MATERI SATUAN WAKTU SDN KANIGARAN 3 - Ayu Maqfiro, Dinda; Fadilah, Yulina (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Mathematics is one of the subjects at school that plays an important role in everyday life. Mathematics learning can be connected to its application in technology and life so that students can view mathematics as a meaningful science. Learning difficulties occur because students consider mathematics to be a difficult and scary subject. This qualitative research aims to determine the difficulties in learning mathematics with time unit material experienced by students, the causes of difficulties in learning mathematics with time unit material. When teaching mathematics, a person's character and disposition can be fostered or developed. This happens because studying mathematics can improve concentration, develop abilities, express opinions briefly and think rationally in making perfect decisions. Low learning is evidence of difficulties in students' learning, in this case the teacher is a responsible person who should be able to understand the difficulties experienced by students.